2011
DOI: 10.1002/pros.21501
|View full text |Cite
|
Sign up to set email alerts
|

Cyr61 is regulated by cAMP‐dependent protein kinase with serum levels correlating with prostate cancer aggressiveness

Abstract: BACKGROUND Cysteine-rich angiogenic inducer 61 (Cyr61) is an extracellular matrix protein involved in the transduction of growth factor and hormone signaling. Previously, we demonstrated that Cyr61 was highly expressed in prostate cancer (PCa) but that the expression levels were associated with a lower risk of PCa recurrence. In the present study, we demonstrate that serum Cyr61 is a potential biomarker that correlates with PCa aggressiveness. Furthermore, we also explore the potential mechanism underlying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Previously, a study demonstrated that Cyr61 mediates thrombin-induced astrocytoma cell proliferation (40). A recent study described that Cyr61 mediates LPAinduced prostate tumor cell invasion, suggesting that Cyr61 is a potential biomarker correlating with prostate cancer aggressiveness (41). Our results that Cyr61 bridges LPA signaling and integrin signaling, leading to SMC migration, demonstrate that Cyr61 is a potentially important molecule that connects intracellular and extracellular information and thus contributes to atherogenesis.…”
Section: Discussionmentioning
confidence: 49%
“…Previously, a study demonstrated that Cyr61 mediates thrombin-induced astrocytoma cell proliferation (40). A recent study described that Cyr61 mediates LPAinduced prostate tumor cell invasion, suggesting that Cyr61 is a potential biomarker correlating with prostate cancer aggressiveness (41). Our results that Cyr61 bridges LPA signaling and integrin signaling, leading to SMC migration, demonstrate that Cyr61 is a potentially important molecule that connects intracellular and extracellular information and thus contributes to atherogenesis.…”
Section: Discussionmentioning
confidence: 49%
“…PCR reactions were subjected to hot start at 95 °C for 3 min followed by 45 cycles of denaturation at 95 °C for 10 s, annealing at 60 °C for 30 s, and extension at 72 °C for 30 s using the CFX96 Real-Time PCR Detection System (Bio-Rad Laboratories, Inc.). PCR primers were 5′- CGTAAAGTAGAAGGTGATTG -3′ (forward) and 5′- ATGCTTAGGATTAGGTGGAG -3′ (reverse) for PAGE4, 5′- TAACAGT GGGTGCCAACTCA -3′ (forward) and 5′- TTTTTCTCTCCGTCGCAACT -3′ (reverse) for c-Jun and 5′- GAATATAATCCCAAGC GGTTTG -3′ (forward) and 5′- ACTTCACATCACAGCTCCCC -3′ (reverse) for TATA binding protein (TBP)[45]. Analysis and fold differences were determined using the comparative threshold cycle method.…”
Section: Methodsmentioning
confidence: 99%
“…We found that Cyr61 expression in PCa was modulated by oncogenic ‘stimulation’ such as androgens or lysophosphatidic acid, as well as anti-oncogenic ‘stress’ such as serum starvation or phosphoinositide 3-kinase inhibition in the tumor environment. 37 These results suggest that differences in Cyr61 expression may reflect the extracellular environmental status of the cancer, which is distinct between PCa and breast cancer.…”
Section: Cyr61 As a Prognostic Tissue Markermentioning
confidence: 88%
“…Cyr61 levels were significantly higher in NOC-PCa (116.3±140.2 ng ml −1 ) than in OC-PCa (79.7±56.0 ng ml −1 ), although PSA levels were not significantly different (6.4±3.8 ng ml −1 in OC-PCa and 6.1±4.7 ng ml −1 in NOC-PCa, P =0.376) (Figure 2a). 37 Serum Cyr61 levels are not correlated with serum PSA levels and may increase the accuracy for differentiating NOC-PCa from OC-PCa combined with serum PSA levels and other clinical parameters used in PCa staging nomograms. 39 However, serum Cyr61 levels tended to be higher in control patients compared with OC-PCa patients.…”
Section: Cyr61 As a Serum Markermentioning
confidence: 98%
See 1 more Smart Citation